Home blood pressure normalcy: The Didima study - Stergiou, George S; Thomopoulou, Georgia C; Skeva, Irini I; Mountokalakis, Theodore D (American journal of hypertension, 2000)
To evaluate reference values of home blood pressure (HBP) a cross-sectional community study was conducted on 694 adult subjects (aged ≥ 18 years) of the village Didima in southern Greece (participation rate 76.4%). Clinic blood pressure (CBP) was measured on two visits (triplicate measurements, mercury sphygmomanometer) and HBP on 3 workdays (duplicate morning and evening measurements, oscillometric devices; Omron HEM 705CP). After exclusion of 132 subjects (103 treated hypertensives and 29 with incomplete data), 562 subjects were analyzed (mean ± SD aged 51.2 ± 17.2 years, 42.7% men). Average HBP (120.0 ± 17.8/72.6 ± 8.8 mm Hg, systolic/diastolic) was strongly correlated ( P < .0001) with CBP (118.7 ± 17.7/73.8 ± 10.5 mm Hg). Systolic CBP was 1.3 mm Hg lower than HBP ( P < .01, 95% confidence interval 0.4, 2.2), whereas diastolic CBP was 1.2 mm Hg higher than HBP ( P < .0001, 95% confidence interval 0.6, 1.7). The threshold of HBP normality determined using three different approaches was 1) 139.7/83.0 mm Hg (systolic/diastolic) using the distribution criterion (95th percentile of the HBP distribution among 476 normotensive subjects); 2) 139.7/85.8 mm Hg using the correspondence criterion (the percentiles of the CBP distribution that correspond to CBP ≥ 140/90 mm Hg were estimated, and the levels of BP that correspond to these same percentiles on the HBP distribution were calculated); and 3) 137.4/82.7 mm Hg using the regression criterion (calculation of the levels of HBP that correspond to CBP of 140/90 mm Hg using the regression equation between HBP and CBP). Overall, the findings of the three criteria suggest that average HBP < 137/82 mm Hg might be considered as probably normal, > 140/86 mm Hg as probably abnormal, and within these limits as borderline. Until mortality-based prospective data are available, this approach might be useful in the interpretation of HBP in clinical practice.